An Evaluation of Actinide Reactivity with CO2, O2, and O2/He Gases using Inductively Coupled Plasma Tandem Mass Spectrometry: Application to Simultaneous Measurement of 241Am/241Pu Ratios in Unseparated Complex Matrices - Schlieder, Tyler D.; Hobbs, Kirby P.; French, Amanda D.; Hughes, Lee H.; Arnquist, Isaac J.; Beck, Chelsie (Analytical chemistry (Washington), 2025)
Accurate actinide measurements are critical within the field of nuclear science. Traditional methods for actinide quantification require time-consuming sample processing prior to analysis. There is a need for rapid analytical techniques that still maintain a high degree of accuracy. In this work, actinide reactivity was assessed for multiple oxygen-containing reaction gases using quadrupole inductively coupled plasma tandem mass spectrometry (Q-ICP-MS/MS) to evaluate actinide analysis in complex sample matrices without analyte-matrix separation. A novel method was developed to measure 241Am/241Pu in complex sample matrices using an O2/He reaction gas with no matrix removal or analyte preconcentration. This inline method reduces matrix-derived polyatomic interferences that complicate traditional ICP-MS analyses by mass-shifting to 241Am16O+ and 241Pu16O2 +, allowing Am and Pu to be mass separated for simultaneous analysis. While mass shifting is efficient, a small portion of Am+ (<1.3%) and Pu+ (<1.4%) react to form AmO2 + and PuO+, respectively. Therefore, a mass balance approach was used, in combination with reactivity determined from 242Pu and 243Am standard solutions, to correct for residual 241PuO+ and 241AmO2 +. The method was validated by measuring 241Am/241Pu in Pu isotope standards CRM-136 and CRM-137 (separated in March/April 1970 and February 2022, respectively) in both neat solutions and complex matrices containing diluted soil (NIST SRM 2711a, > 1000 μg·g–1). Method detection limits of 15.9 and 9.6 fg·g–1 were determined for 241Am and 241Pu, respectively, and 241Am/241Pu ratios were measured with accuracies within <3.5%. This work presents the first direct analysis of 241Am/241Pu in unseparated complex matrices, advancing the capabilities for rapid actinide measurements.